Edukasi Pemanfaatan Limbah Kardus menjadi Produk Kerajinan Tangan Bernilai Ekonomi di Kelurahan Tamangapa, Kota Makassar: Education on the Utilization of Cardboard Waste into Handicraft Products with Economic Value in RW.05, Tamangapa Village, Makassar City - Arsyad, Nashrah; Dewi, Ratna; Said, Juhana (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Utilization of cardboard waste In addition to helping reduce the pile of garbage, cardboard waste can also be processed into aesthetic and economically valuable handicraft products. To utilize cardboard waste, it needs to be supported by knowledge and skills in processing it. This PKM activity aims to provide education on using cardboard waste in handicraft products. The target of the PKM program is aimed at residents of RT 02. RW. 05, Tamangapa Village who live not far from the Tamangapa TPA. The method of implementing PKM activities is carried out by providing education and technical guidance on making handicraft products from cardboard waste. The results of implementing this activity are increasing public awareness of the importance of waste management. This can be seen from the enthusiasm of the participants in participating in the entire series of activities and their active participation in the production process. In addition, this activity also succeeded in improving the skills of participants in processing cardboard waste into products that have aesthetic and economic value.